PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN HUMAN CAPITAL MANAGEMENT PT PERUSAHAAN GAS NEGARA TBK - Nazwa Nurshadrina; Siti Rahmawati (Journal of Management Small and Medium Enterprises (SME's), 2024)
PT Perusahaan Gas Negara Tbk (PGN) had a strong organizational culture and a focus on employee job satisfaction, demonstrating that effective human resource management contributed to the company's operations and the achievement of strategic goals. This satisfaction was the result of excellent Human Capital Management (HCM), which provided strategies and practices to improve performance and achieve company goals. This research aims to analyze the influence of organizational culture and job satisfaction on the performances of HCM employees of PT Perusahaan Gas Negara Tbk using descriptive analysis methods, Structural Equation Modeling- Partial Least Square (SEM-PLS), and simultaneous tests. The sampling method used is non-probability sampling with a saturated sampling type. The research result showed that the organizational culture, job satisfaction, and performances of HCM employees of PT Perusahaan Gas Negara Tbk are categorized as high. Organizational culture affected performance, job satisfaction had no effect on performance, and simultaneously, organizational culture and job satisfaction affected performance.